Beban Kerja Fisik dan Iklim Kerja dengan Status Hidrasi Pekerja Unit P2 Bagian (Wood Working 1) WW1 PT. KTI Probolinggo - Denti Tarwiyanti; Ragil Ismi Hartanti; Reny Indrayani (Pustaka Kesehatan, 2020)
High work climate and high workload can cause overstress and metabolic heat in the body wich will potentially affect workers hydration status. Industrial workers often carry out physical work in hot working environments with high workload (physical workload) over a long period. Loading and a high work climate can cause overstress and metabolic heat so that workers have the potention dealing with heat stress and dehydration due to excessive sweating issue and it will affect the workers hydration status. This study purpose was to find out the relationship between physical workload and work climate due to workers hydration status unit P2 (wood working 1) WW1 section in PT. KTI Probolinggo. This study used quantitative approach, an observational analytic type with cross sectional design. Based on statistical tests result using Spearman and Chi Square, the factors associated to hydration status were age with a positive linkage direction and drinking water consumption with a negative linkage direction. Unrelated factors were gender (p value = 0.688), nutritional status (p value = 0.333), years of service (p value = 0.626), physical workload (p value = 0.333), and work climate (p value = 0.105). The advice given based on this research is adding more water consumption, adding glasses according to the number of workers and drinking water needs of each worker, providing education of body fluid needs for hot working environments including signs of dehydration and how to prevent it, setting-up diagram poster shows the importance of drinking water consumption in hot working environment. Keywords : Physical Workload, Work Climate, Hydration Status.